Pengaruh Stres Kerja Terhadap Semangat Kerja Pegawai Pada Dinas Pekerjaan Umum Dan Perumahan Rakyat Kabupaten Bima - Sukarman Sukarman; Ikbal Irawan (Pusat Riset dan Inovasi Nasional, 2023)
Human resources are the potential contained within humans to realize their role as adaptive and transformative social living beings. Human resources are able to manage themselves and all the potential contained in nature towards achieving a prosperous life in a balanced and sustainable order. The latest developments currently view human resources as no longer mere resources, but rather as capital or assets for institutions or organizations (Sedarmayati, 2012)